An Overview of MPLS Technology: Quality of Service and Traffic Engineering - Fusario, Rubén J. (2007)
This paper provides an overview of Multi-Protocol Label Switching Technology (MPLS). Distinctive issues are presented as well as Quality of Service (QoS). Traffic Engineering (TE) features are discussed. It also describes current network trends where Internet Protocol (IP) is the predominant technology and points out the advantages of MPLS for data, voice, and video information transport.